Correlation Analysis between Understanding Biochemistry Concepts and Chemistry Education Students' Problem-Solving Skills through Validated HOTS Instruments - Mariati; Insan Nuhari (Jurnal Penelitian Pendidikan IPA, 2026)
Understanding biochemistry concepts and problem-solving skills are essential competencies for chemistry education students in facing the demands of 21st-century science learning. However, empirical evidence regarding the relationship between these competencies measured through Higher Order Thinking Skills (HOTS)-based instruments remains limited. This study aimed to analyze the correlation between students’ understanding of biochemistry concepts and their problem-solving skills using validated HOTS instruments. A quantitative correlational design was employed involving 60 Chemistry Education students who had completed the Biochemistry course. Data were collected using a HOTS-based biochemistry concept understanding test and a HOTS-based problem-solving skills test. The instruments were validated by experts and tested for reliability. Data were analyzed using descriptive statistics and Pearson correlation analysis after fulfilling normality and linearity assumptions. The results showed that the mean score of biochemistry concept understanding was 72.35 (SD = 8.42), while the mean score of problem-solving skills was 68.10 (SD = 9.15). The normality and linearity tests indicated that the data met the requirements for parametric analysis. Pearson correlation analysis revealed a positive and significant correlation between biochemistry concept understanding and problem-solving skills (r = 0.63, p < 0.05). Furthermore, the coefficient of determination (r² = 0.40) indicated that understanding biochemistry concepts contributed 40% to the variance in students’ problem-solving skills. These findings demonstrate that stronger conceptual understanding is associated with better problem-solving performance. In conclusion, understanding biochemistry concepts significantly contributes to the development of students’ problem-solving skills. Therefore, integrating HOTS-oriented learning and assessment into biochemistry instruction is recommended to enhance conceptual mastery and higher-order thinking skills among prospective chemistry teachers.